3-(Adamantan-1-yl)-4-ethyl-1-{[4-(2-methoxyphenyl)piperazin-1-yl]methyl}-1H-1,2,4-triazole-5(4H)-thione - El-Emam, Ali A.; Al-Tuwaijri, Hanaa M.; Al-Abdullah, Ebtehal S.; Chidan Kumar, C. S.; Hoong, Kun Fun (International Union of Crystallography, 2014)
In the title compound, C26H37N5OS, the piperazine ring adopts a chair conformation. The triazole ring forms dihedral angles of 67.85 (9) and 59.41 (9) with the piperazine and benzene rings, respectively, resulting in an approximate Vshaped conformation for the molecule. An intramolecular C— H...O hydrogen bond generates an S(6) ring motif. The crystal structure features C—H...n interactions, producing a two-dimensional supramolecular architecture.